Enzymes of α,α-Trehalose Metabolism in Soybean Nodules - Salminen, Seppo O. (1986)
Metabolism of trehalose, α,d-glucopyranosyl-α,d-glucopyranoside, was studied in nodules of Bradyrhizobium japonicum-Glycine max [L.] Merr. cv Beeson 80 symbiosis. The nodule extract was divided into three fractions: bacteroid soluble protein, bacteroid fragments, and cytosol. The bacteroid soluble protein and cytosol fractions were gel-filtered. The key biosynthetic enzyme, trehalose-6-phosphate synthetase, was consistently found only in the bacteroids. Trehalose-6-phosphate phosphatase activity was present both in the bacteroid soluble protein and cytosol fractions. Trehalase, the most abundant catabolic enzyme was present in all three fractions and showed two pH optima: pH 3.8 and 6.6. Two other degradative enzymes, phosphotrehalase, acting on trehalose-6-phosphate forming glucose and glucose-6-phosphate, and trehalose phosphorylase, forming glucose and β-glucose-1-phosphate, were also detected in the bacteroid soluble protein and cytosol fractions. Trehalase was present in large excess over trehalose-6-phosphate synthetase. Trehalose accumulation in the nodules would appear to be predicated on spatial separation of trehalose and trehalase.